PRINSIP-PRINSIP HUKUM ISLAM DALAM KETATANEGARAAN INDONESIA - Maureen Linus (Jurnal Hukum Adigama, 2021)
Indonesia is the world’s fourth-most populous country and the most populous Muslim majority country. Indonesia is a presidential, constitutional republic with an elected legislature. It is known that Islam is the largest religion in Indonesia with the percentage reaching the number 86.7% . With the huge number of the Muslim population, some part of Indonesia uses the Islamic law as their legal system. The state constitution in Indonesian legal system differs a lot from the Islamic legal system but some parts of Indonesia use the Islamic law as their legal system. The Islamic legal system also known as the sharia law co-exist together overcoming the vast differences between the Indonesian and the Islamic legal system. This paper aims to describe and discuss the vast differences of the state constitution between the Islamic legal system and the Indonesian legal system as well as how it co-exist together within the area of Indonesia and how it affects the Indonesian constitution.